Proteomic Profiling of Black Coral (Antipatharia) Skeleton Reveals Hundreds of Skeleton-Associated Proteins Across Two Taxa - Drake, Jeana L.; Mass, Tali (Frontiers in Marine Science, 2022)
Black corals, ecologically important cnidarians found from shallow to deep ocean depths, form a strong yet flexible skeleton of sclerotized chitin and other biomolecules including proteins. The structure and mechanical properties of the chitin component of the skeleton have been well-characterized. However, the protein component has remained a mystery. Here we used liquid chromatography-tandem mass spectrometry to sequence proteins extracted from two species of common Red Sea black corals following either one or two cleaning steps. We detected hundreds of proteins between the two corals, nearly 70 of which are each other’s reciprocal best BLAST hit. Unlike stony corals, only a few of the detected proteins were moderately acidic (biased toward aspartic and/or glutamic acid residues) suggesting less of a role for these types of proteins in black coral skeleton formation as compared to stony corals. No distinct chitin binding domains were found in the proteins, but proteins annotated as having a role in protein and chitin modifications were detected. Our results support the integral role of proteins in black coral skeleton formation, structure, and function.